The Fortress Cities on the Onega in the XVII Century - Bode, Andrei (project baikal, 2019)
In the 17th century Onega fortress cities of Kargopol, Ust-Mosha and Turchasovo represented a single system of fortified points, connected historically, economically and geographically. Analysis of town planning and its relationship to the landscape allows us to conclude that these cities were built according to a unified model and had similar planning characteristics. The space planning of the Onega cities shows organic connection between the regular and the natural-landscape aspects, which is a distinguishing feature of ancient Russian town planning. Also the construction of the walls of the first two stages of Kargopol fortress and the walls of Ust-Mosha and Turchasovo fortresses is considered, which is especially important for a more complete understanding of its evolution.
Keywords: Russian town planning; layout; wooden architecture; fortification; typology